PEMBELAJARAN MENGGUNAKAN RECIPROCAL TEACHING : MENINGKATKAN HIGHER ORDER THINKING SKILLS (HOTS) DAN SELF CONFIDENCE PESERTA DIDIK - Hidayah, Nur; Khotimah, Khusnul; Novitasari, Aulia (Universitas Cokroaminoto Palopo, 2024)
Field studies show that students' higher order thinking skills (HOTS) and self-confidence are still low. This research aims to determine the impact of using the reciprocal teaching model on students' higher order thinking skills (HOTS) and self-confidence. In its implementation, this research used a quasi-experimental method. There are two classes used, namely the control class and the experimental class, namely XI IPA 1 and XI IPA 2 which were obtained using the cluster random sampling technique. The experimental class uses a reciprocal teaching learning model and the control class uses a direct instruction learning model. The instruments used in this research were tests and questionnaires. The test instrument is to measure students' HOTS, while the questionnaire instrument is to measure students' self-confidence. Based on the results of the hypothesis test, the sig value is obtained. 0.000 < 0.05 so it can be seen that the reciprocal teaching learning model can be used to increase students' HOTS and self-confidence.